High speed and ultra-low dark current Ge vertical p-i-n photodetectors on an oxygen-annealed Ge-on-insulator platform with GeOx surface passivation - Son, Bongkwon (2020)
Germanium (Ge) vertical p-i-n photodetectors were demonstrated with an ultra-low dark current of 0.57 mA/cm2 at -1 V. A germanium-on-insulator (GOI) platform with a 200-mm wafer scale was realized for photodetector fabrication via direct wafer bonding and layer transfer techniques, followed by oxygen annealing in finance. A thin germanium-oxide (GeOx) layer was formed on the sidewall of photodetectors by ozone oxidation to suppress surface leakage current. The responsivity of the vertical p-i-n annealed GOI photodetectors was revealed to be 0.42 and 0.28 A/W at 1,500 and 1,550 nm at -1 V, respectively. The photodetector characteristics are investigated in comparison with photodetectors with SiO2 surface passivation. The surface leakage current is reduced by a factor of 10 for photodetectors via ozone oxidation. The 3dB bandwidth of 1.72 GHz at -1 V for GeOx surface-passivated photodetectors is enhanced by approximately 2 times compared to the one for SiO2 surface-passivated photodetectors. The 3dB bandwidth is theoretically expected to further enhance to ∼70 GHz with a 5 µm mesa diameter.